Gut-mammary pathway: Breast milk microbiota as a mediator of maternal gut microbiota transfer to the infant gut - Lulu Meng; Haishan Xie; Zhe Li; Kian Deng Tye; Ge Fan; Ting Huang; Hao Yan; Xiaomei Tang; Huijuan Luo; Xiaomin Xiao (Journal of Functional Foods)
This observational study investigated the transfer of maternal gut microbiota to the infant gut through breast milk and its implications for infant gut health. Fecal and breast milk samples were collected from 23 healthy mother-infant pairs, with 11 breast milk samples testing positive for microbial presence. Microbial source tracking revealed that 22.89 % of breast milk microbiota originated from the maternal gut, and 25.64 % of the infant gut microbiota was derived from breast milk. Shared OTUs between the paired maternal gut, breast milk, and infant gut had a median of 109 (range: 61–148). Genera such as Bifidobacterium, Escherichia-Shigella, and Bacteroides were common across the three sites. Comparisons with the sterile milk group (n = 12) indicated a potential role for breast milk microbiota in maternal-infant microbiota transmission. This study highlights breast milk as a significant medium for microbiota transfer and provides a theoretical basis for promoting infant gut health.